Hubungan Tekanan Darah yang Tidak Terkontrol dengan Kejadian Gangguan Kognitif pada Lansia - Yuwono Yuwono; Fernando Nathaniel; Joshua Kurniawan; Noer Saelan Tadjudin (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Hypertension is one of the cardiovascular disease, defined by World Health Organization as blood pressure ≥140/90 mmHg. The high prevalence of hypertension has always been a problem globally. This disease could cause many complications, including cerebrovascular disease, and often associated with cognitive impairment. This study is done to find out the relation between uncontrolled blood pressure and cognitive impairment in geriatric people. This study is an observational analytic study with cross-sectional design. Samples are geriatric people with minimum of 60 years of age in Sasana Tresna Werda RIA Pembangunan in January 2019. Sample was taken with total sampling method. The hypertension criteria in study is previous history of hypertension or blood pressure ≥140/90 mmHg. MMSE score interpretations are: (1) score of 25-30: normal cognitive function; (2) score of <21: indication of mild to severe cognitive impairment. Statistical analysis used in the study are Pearson Chi Square with Yates Correction, with alternative of Fischer Exact, with parameter of expected count of 5%. Significant relation expected in the study is 5%. The study found that there are no significant relation between history of hypertension with cognitive impairment in geriatric people in Sasana Tresna Werda RIA Pembangunan (p-value=0.098), but it is predicted that the group of geriatric people with history of hypertension has 27.7% more risk of getting cognitive impairment. However, the elderly group who have a history of hypertension has a proportion of 27.7% experiencing cognitive impairment.